Prevalence of Goiter and Urinary Iodine in Schoolchildren of Hamadan Province in 2001 - Fereydun Azizi (پزشکی بالینی ابن سینا, 2006)
Introduction & Objective: The province of Hamadan was one of the regions with endemic goiter in Iran. Following initiation of the program of control of iodine deficiency in 1989, production, distribution and consumption of iodized salt were begun.